Ambulatory blood pressure monitoring in pediatric renal transplantation - Seeman, Tomáš (Current hypertension reports, 2012)
Hypertension is a common and serious complication after renal transplantation. It is an important risk factor for graft loss and adverse cardiovascular outcomes. Blood pressure (BP) in transplanted children should be measured not only by clinic BP (cBP) measurement, but also by ambulatory blood pressure monitoring (ABPM), because ABPM has distinct advantages over cBP, specifically the ability to reveal nocturnal, masked or white-coat hypertension. These types of hypertension are common in transplanted children (nocturnal hypertension 36-71 %, masked hypertension 24-45 %). It may also reveal uncontrolled hypertension in treated children, thereby improving control of hypertension. Regular use of ABPM and ABPM-guided therapy of hypertension may help to decrease cardiovascular and renal target organ damage in transplanted children. Therefore, ABPM should be routinely performed in all transplanted children at least once a year, regardless of the values of cBP.
Keywords: lidé; hypertenze; ambulantní monitorování krevního tlaku; pooperační komplikace; transplantace ledvin; dítě; Masked Hypertension; Blood Pressure Monitoring, Ambulatory; Kidney Transplantation; přežívání štěpu; Postoperative Complications; Humans; maskovaná hypertenze; Graft Survival; Hypertension; syndrom bílého pláště; Time Factors; časové faktory; Child; White Coat Hypertension